Design Science Approach to Management - Baran, Grzegorz (Contemporary organisation and management. Challenges and trends, 2020)
The paper concerns the methodological basis of research for creating knowledge in management sciences understood as practical sciences or design sciences. The aim of this paper is to introduce research framing in management sciences, which takes into account that the conventional approaches to management regarded as an explanatory science are not sufficient to fully examine and deal with contemporary ill-structured, complex, unambiguous and often open management and organization problems. The aim has been realized using existing knowledge within a conceptual research framework for intellectual deliberation on the presented approach.